Analysis of students' scientific writing skills in the biology education study program at Sebelas Maret University - Dwi Oetomo; Sri Widoretno; Murni Ramli; Baskoro Adi Prayitno; Bowo Sugiarto; Chandra Adi Prabowo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
: Scientific writing skills were an essential competency for biology students in preparing effective research reports because they enabled students to communicate their research findings clearly and professionally. These skills were crucial for ensuring that students could present their work in a manner that adhered to scientific standards, facilitated peer review, and contributed to the broader scientific community. Additionally, strong scientific writing skills helped students develop critical thinking and analytical abilities, which were necessary for interpreting data and drawing valid conclusions. This competency also prepared students for future academic and professional endeavors, where the ability to articulate scientific concepts and results was highly valued. This research aimed to describe scientific writing skills, identify obstacles faced, and develop recommendations for learning strategies that could improve the scientific writing skills of Biology education students in 2021, or semester 6, in biology research courses at Sebelas Maret University in preparing reports. The research method used a quantitative approach with a descriptive design. Indicators analyzed included creative content development, use of relevant and trustworthy references, communication of necessary knowledge, and connecting science and technology with everyday life. Data were collected through assessing biology research reports from Biology Education Study Program students. The research results showed that the average score of students' scientific writing skills was 67.5 on a scale of 100, with the majority of students in the sufficient category. Students still experienced difficulties in finding and evaluating credible sources to support their arguments in scientific writing, as well as difficulties in describing the practical implications of their research. This study suggested implementing more interactive, project-based learning and providing constructive feedback to improve scientific writing skills in a more comprehensive manner.